Smoking‐Induced M2‐TAMs, via circEML4 in EVs, Promote the Progression of NSCLC through ALKBH5‐Regulated m6A Modification of SOCS2 in NSCLC Cells - Cheng Cheng; Peiwen Wang; Yi Yang; Xuan Du; Haibo Xia; Jinyuan Liu; Lu Lu; Hao Wu; Qizhan Liu (Advanced Science, 2023)
Abstract Lung cancer is a commonly diagnosed disease worldwide, with non‐small cell lung cancers (NSCLCs) accounting for ≈ 85% of cases. Cigarette smoke is an environmental exposure promoting progression of NSCLC, but its role is poorly understood. This study reports that smoking‐induced accumulation of M2‐type tumor‐associated macrophages (M2‐TAMs) surrounding NSCLC tissues promotes malignancy. Specifically, extracellular vesicles (EVs) from cigarette smoke extract (CSE)‐induced M2 macrophages promoted malignancy of NSCLC cells in vitro and in vivo. circEML4 in EVs from CSE‐induced M2 macrophages is transported to NSCLC cells, where it reduced the distribution of ALKBH5 in the nucleus by interacting with Human AlkB homolog H5 (ALKBH5), resulting in elevated N6‐methyladenosine (m6A) modifications. m6A‐seq and RNA‐seq revealed suppressor of cytokine signaling 2 (SOCS2)‐mediated activation of the Janus kinase‐signal transducer and activator of transcription (JAK‐STAT) pathway by regulating m6A modification of SOCS2 via ALKBH5. Down‐regulation of circEML4 in EVs from CSE‐induced M2 macrophages reversed EVs‐enhanced tumorigenicity and metastasis in NSCLC cells. Furthermore, this study found that smoking patients showed an increase in circEML4‐positive M2‐TAMs. These results indicate that smoking‐induced M2‐TAMs via circEML4 in EVs promote the NSCLC progression through ALKBH5‐regulated m6A modification of SOCS2. This study also reveals that circEML4 in EVs from TAMs acts as a diagnostic biomarker for NSCLC, especially for patients with smoking history.